Evaluasi Overhaul terhadap Konsumsi HSD PLTDG Pesanggaran - Eri Prabowoa; Trassanda Scudetto Widestomo Putra; Indra Kusumah Disastra (JTM : JURNAL TEKNIK MESIN, 2026)
High Speed Diesel (HSD) consumption is a critical operating variable for diesel-gas power plants because it directly affects fuel cost, engine performance, and generating-unit reliability. This article evaluates HSD fuel consumption of the Wartsila 18V50DF engine at PLTDG 200 MW Pesanggaran, Bali, before and after overhaul. The study uses quantitative analysis of performance-test data from Unit 02 and Unit 05 at several operating-hour intervals. Calculations include effective power, indicated power, charge efficiency, combustion-air requirement, air-fuel ratio, hourly fuel consumption, and brake specific fuel consumption. The results show that overhaul reduced HSD consumption in all observed comparisons. Unit 02 decreased from 4888.91 to 2653.98 L/h at 18000 h, from 6425.42 to 4330.17 L/h at 36000 h, and from 5168.27 to 5098.43 L/h at 48000 h. Unit 05 decreased from 4330.19 to 4260.32 L/h at 36000 h and from 5517.48 to 5168.27 L/h at 48000 h. The improvement is associated with restoration of combustion components, cleaner air supply, and reduced combustion deposits after overhaul.